The holistic frame of designing smart, connected products: A systematic literature review and expert interview. (4th May 2022) - Xihui Liu, Sylvia; Zhang, Mengting; de Bont, Cees
Abstract: With the transformation led by the Fourth Industrial Revolution, the nature of product innovation has shifted from traditional physical products to smart products or Smart, Connected Product (SCP). There is not a comprehensive understanding of SCP since it is proposed in 2014. And, this is a new and unfamiliar arena for designers. To fill the gap in the research, a holistic frame of SCP was established based on explored product attributes through systematic literature review and expert interview. As a result, 20 attributes and 44 sub-attributes were obtained and classified into four clusters— Appearance, Function, Experience and Meaning . It explains the concepts and four capabilities of SCP, as well as guides designers' practice on developing new ideas of SCP.